Adjuvant chemotherapy is associated with improved postoperative survival in specific subtypes of invasive intraductal papillary mucinous neoplasms (IPMN) of the pancreas: it is time for randomized controlled data. Issue 5 (May 2019) - Marchegiani, Giovanni; Andrianello, Stefano; Dal Borgo, Chiara; Secchettin, Erica; Melisi, Davide; Malleo, Giuseppe; Bassi, Claudio; Salvia, Roberto
Abstract: Background: Very little is known about adjuvant chemotherapy for invasive Intraductal Papillary Mucinous Neoplasms (IPMNs) of the pancreas. The aim was to assess whether adjuvant chemotherapy affects survival. Methods: Retrospective evaluation of invasive IPMNs. Patients treated with surgery alone or followed by adjuvant chemotherapy were compared in terms of survival. Results: A total of 102 invasive IPMNs were analyzed. Median follow-up was 72 (5–318) months and 18.6% received adjuvant chemotherapy. Overall, recurrence rate was 40.2%, while 5-year overall survival and disease specific survival (DSS) were 65.3% and 69.4%, respectively. N1 disease (HR5.58, CI95% 2.49–12.51, p < 0.01), tubular type (HR2.35, CI95% 1.71–4.82, p = 0.05) and G3 tumors (HR4.54, CI95% 2.12–15.49, <0.01) were predictors of reduced DSS. Overall, there was no difference in the 5-year DSS comparing patients treated with adjuvant chemotherapy to surgery alone (61.8 vs. 69.4%, p = 0.8). Adjuvant chemotherapy significantly improved DSS only in N1 (5-years-DSS 76 vs. 35.8%, p = 0.01) and tubular carcinomas (5-years-DSS 88.9 vs. 53%, p = 0.03). Conclusions: Adjuvant therapy improves survival only in invasive IPMNs with nodal disease or tubular differentiation. Future trials are needed to improve the level of evidence about adjuvant chemotherapy.